Paper tube zoo :helping children learn (viva education) - Moore, Jo Ellen; Evans, Joy (Viva Education New Delhi, 2010)
Helping Children Learn introduces young readers to diverse art forms from different cultures, encouraging creativity and cultural understanding. Through engaging activities and illustrations, children can explore traditional crafts and learn about the rich heritage of various communities.